Diseases in pet guinea pigs: a retrospective study in 1000 animals. (22nd August 2015) - Minarikova, A.; Hauptman, K.; Jeklova, E.; Knotek, Z.; Jekl, V.
Abstract : Guinea pigs are commonly kept as pet animals; however, information about particular disease prevalence is lacking. The objective of this article was to present disease prevalence in 1000 pet guinea pigs from private owners divided into three age groups: under two years; between two and five years; and above five years. Medical records of guinea pigs ( Cavia aperea f. porcellus ) that were presented to the authors' clinic in the period from January 2008 to August 2013 were reviewed. The most commonly diagnosed disease in guinea pigs was dental disease (36.3 per cent), with higher prevalence in the middle age group (P<0.001) and in males (P<0.001) rather than females. Skin problems were seen as the second most common disease (33.3 per cent), with higher prevalence in male guinea pigs (P<0.001) and in animals younger than two years (P<0.001). Ovarian cystic disease was the third most commonly seen disorder, with higher prevalence in females older than two years (P<0.001). Other common health disorders included gastrointestinal stasis, heterotopic ciliary body calcifications, fatty eye and tibiofemoral osteoarthritis. Only 81 guinea pigs from a total of 1000 animals were healthy. This is the first study to describe the disease prevalence in three age groups of pet guinea pigs.